ANALISIS KEPERCAYAAN DIRI ANAK TERHADAP KEMAMPUAN INTERAKSISOSIAL ANAK USIA DINI DI TKK MARIA GUNUNG KARMEL SATAP SDK NARU - Marsiana Mbupu; Konstantinus Dua Dhiu; Efrida Ita; Elisabeth Tantiana Ngura (STKIP Pesisir Selatan, 2026)
This study aims to analyze the relationship between children's self-confidence and the social interaction skills of early childhood at TKK Maria Gunung Karmel Satap SDK Naru. The background of this study is based on the variation in children's self-confidence levels, which impact the quality of their social interactions in the school environment. The research method used in this study is a qualitative method with a descriptive approach. The study population was all early childhood children at the school, with a total sampling technique. Data collection was conducted through observation, interviews, and documentation. The data analysis technique used an interactive analysis model that includes three main stages: data reduction, data presentation, and conclusion drawing. The results show that children's self-confidence levels vary, and there is a significant positive relationship between self-confidence and social interaction skills. Children with high self-confidence tend to be more active, able to cooperate, have the courage to communicate, and are more adaptable to their social environment. These findings indicate that strengthening self-confidence from an early age is crucial for supporting optimal children's social development.